PID controller tuning by differential evolution algorithm on EDM servo control system - Andromeda, Trias (2013)
Maintaining gap between Electrode and workpiece in Electrical Discharge Machining (EDM) is very important since the capability of control system to keep the gap will improve the performance of this machine. Therefore to maintain the gap, a Proportional Integral Derivative (PID) controller is designed and applied to EDM servo actuator system. The objective of this work is to obtain a stable, robust and controlled system by tuning the PID controller using Differential Evolution (DE) algorithm. The controller for EDM die sinking is verified by simulation of the control system using MATLAB/Simulink program. Simulation results verify the capabilities and effectiveness of the DE algorithm to search the best configuration of PID parameters controller to control the electrode position.